2015
DOI: 10.1051/0004-6361/201525846
|View full text |Cite
|
Sign up to set email alerts
|

Mg line formation in late-type stellar atmospheres

Abstract: Context. Magnesium is an element of significant astrophysical importance, often traced in late-type stars using lines of neutral magnesium, which is expected to be subject to departures from local thermodynamic equilibrium (LTE). The importance of Mg, together with the unique range of spectral features in late-type stars probing different parts of the atom, as well as its relative simplicity from an atomic physics point of view, makes it a prime target and test bed for detailed ab initio non-LTE modelling in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 97 publications
(145 reference statements)
12
130
1
Order By: Relevance
“…We found an average difference of 0.08 dex for Arcturus, with extreme cases of around 0.15 dex for the lines at λ8712 and λ8717 Å. Osorio et al (2015) also discussed that 3D effects become strong as well, making it more difficult to make a one-to-one comparison with our case.…”
Section: Magnesiummentioning
confidence: 54%
See 2 more Smart Citations
“…We found an average difference of 0.08 dex for Arcturus, with extreme cases of around 0.15 dex for the lines at λ8712 and λ8717 Å. Osorio et al (2015) also discussed that 3D effects become strong as well, making it more difficult to make a one-to-one comparison with our case.…”
Section: Magnesiummentioning
confidence: 54%
“…NLTE corrections were computed for selected lines of magnesium (Osorio et al 2015), silicon (Bergemann et al 2013 calcium (Lind et al 2013), chromium (Bergemann & Cescutti 2010), and manganese (Bergemann & Gehren 2008). The main uncertainty in these calculations is typically related to the inelastic hydrogen collision rates.…”
Section: Departures From Nltementioning
confidence: 99%
See 1 more Smart Citation
“…This enhances the role that inelastic hydrogen collision rates can play for a NLTE abundance determination. Recently, it has been shown that the chargetransfer (i.e., ion-pair production 4 ) processes can domi-nate over excitation processes (Osorio et al 2015;Osorio & Barklem 2016;Ezzeddine et al 2016b). Cross-section calculations for Li+H and Na+H (Barklem et al 2010), for example, have shown that the largest cross sections for excitation are small compared with those for ion-pair production from certain energy states.…”
Section: Iron Model Atommentioning
confidence: 99%
“…It has now been firmly established that Mg lines in spectra of late-type stars are affected by NLTE (Mashonkina 2013). Also, recent works have shown that the effects due to the differences between mean-3D and 1D atmospheric structures are not negligible (Osorio et al 2015). However, it is still unknown whether the combined NLTE and mean-3D effects are large enough to impact the observed [Mg/Fe] distributions in Galactic populations and, consequently, conclusions drawn from the analysis of observed datasets.…”
Section: Introductionmentioning
confidence: 99%